Intestinal multidrug resistance-associated protein 2 is down-regulated in fructose-fed rats - Londero, Ana Sofía; Rigalli, Juan Pablo (The journal of nutritional biochemistry, 2017)
Expression and activity of jejunal multidrug resistance-associated protein 2 (Mrp2) and glutathione-S-transferase (GST) were examined in fructose fed Wistar rats, an experimental model of metabolic syndrome. Animals were fed on (a) control diet or (b) control diet plus 10% w/vol fructose in the drinking water. Mrp2 and the α class of GST proteins as well as their corresponding mRNAs were decreased, suggesting a transcriptional regulation by fructose. Confocal microscopy studies reaffirmed down-regulation of Mrp2. Everted intestinal sacs were incubated with 1-chloro-2,4-dinitrobenzene in the mucosal compartment, and the glutathione-conjugated derivative, dinitrophenyl- S-glutathione (DNP-SG; model Mrp2 substrate), was measured in the same compartment to estimate Mrp2 activity. Excretion of DNP-SG was substantially decreased by fructose treatment, consistent with simultaneous down-regulation of Mrp2 and GST. In addition, the effect of fructose on intestinal barrier function exerted by Mrp2 was evaluated in vivo using valsartan, a recognized Mrp2 substrate of therapeutic use. After intraduodenal administration as a bolus, intestinal absorption of valsartan was increased in fructose-drinking animals. Fructose administration also induced oxidative stress in intestinal tissue as demonstrated by significant increases of intestinal lipid peroxidation end products and activity of the antioxidant enzyme superoxide dismutase, by a decreased GSH/GSSG ratio. Moreover, fructose treatment conduced to increased intestinal levels of the proinflammatory cytokines IL-β1 and IL-6. Collectively, our results demonstrate that metabolic syndrome-like conditions, induced by a fructose-rich diet, result in down-regulation of intestinal Mrp2 expression and activity and consequently in an impairment of its barrier function.